Anti-fatigue activity of a mixture of seahorse (Hippocampus abdominalis) hydrolysate and red ginseng - Nalae Kang; Seo-Young Kim; Sum Rho; Ju-Young Ko; You-Jin Jeon (Fisheries and Aquatic Sciences, 2017)
Abstract Seahorse, a syngnathidae fish, is one of the important organisms used in Chinese traditional medicine. Hippocampus abdominalis, a seahorse species successfully cultured in Korea, was validated for use in food by the Ministry of Food and Drug Safety in February 2016; however. the validation was restricted to 50% of the entire composition. Therefore, to use H. abdominalis as a food ingredient, H. abdominalis has to be prepared as a mixture by adding other materials. In this study, the effect of H. abdominalis on muscles was investigated to scientifically verify its potential bioactivity. In addition, the anti-fatigue activity of a mixture comprising H. abdominalis and red ginseng (RG) was evaluated to commercially utilize H. abdominalis in food industry. H. abdominalis was hydrolyzed using Alcalase, a protease, and the effect of H. abdominalis hydrolysate (HH) on the muscles was assessed in C2C12 myoblasts by measuring cell proliferation and glycogen content. In addition, the mixtures comprising HH and RG were prepared at different percentages of RG to HH (20, 30, 40, 50, 60, 70, and 80% RG), and the anti-fatigue activity of these mixtures against oxidative stress was assessed in C2C12 myoblasts. In C2C12 myoblasts, H2O2-induced oxidative stress caused a decrease in viability and physical fatigue-related biomarkers such as glycogen and ATP contents. However, treatment with RG and HH mixtures increased cell viability and the content of fatigue-related biomarkers. In particular, the 80% RG mixture showed an optimum effect on cell viability and ATP synthesis activity. In this study, all results indicated that HH had anti-fatigue activity at concentrations approved for use in food by the law in Korea. Especially, an 80% RG to HH mixture can be used in food for ameliorating fatigue.